Understanding business - Nickels, William G.; McHugh, James M.; McHugh, Susan M. (8th ed.)
Understanding Business by Nickels, McHugh, and McHugh has been the number one textbook in the introduction to business market for several editions for three reasons: (1) The commitment and dedication of an author team that teaches this course and believes in the importance and power of this learning experience, (2) we listen to our customers, and (3) the quality of our supplements package. From providing the richest most current topical coverage to using dynamic pedagogy that puts students in touch with today's real business issues, to creating groundbreaking and market-defining ancillary items for professors and students alike, Understanding Business leads the way.
Business trends -- Business ownership -- Business management -- Management of human resources -- Marketing -- Managing financial resources.
1
Keywords: industrial management; Business; Business -- Vocational guidance